O cuidado na perspectiva da pessoa portadora de insuficiência renal crônica - Dias, Maria Socorro de Araújo (2001)
The studt aimed to draw tlie attention of people suffering with kidney clironic disease which had not followed tlie recommended therapeutic: dialyse, diet and medicines.As a result of this problem, patients with this disease tend to have a high incidence of morbidity and mortality. The research adopted tlie ethnographic with tlie ethnonursing to guide data collection and analysis. The culture care principies diversity and universality theory contributed more closely to analyse the implications for nursing care and intervention in this particular situation. With tlie help of nine patients, tlie data were collected by means of participant observation, interviews and oficial documents. The findings showed that patients have a strong belief on God helping them to overcome tlie barriers of Life. Also it was foiiiid that some social and cultural factors influence on the way the patients care themselves. Patients consider health the opposite of biological disease, being therapy the main result of tlieir recovery, and health professionals are the only ones who have the ability to take care of them. However, few patients felt that taking care of themselves meant liberty and not living in function ofthe disease. In conclusion data helped to understand that the process of adoption of full therapy depends on the meaning of economic, social and cultural factors attributed by patients within their context. The nursing care must observe the implications of people's cultural influence and the health education can help them to make decisions on self-care.